P1059Recurrence of AF after pulmonary vein isolation: how many times?. (18th June 2020) - Silverio Antonio, P; Cortez-Dias, N; Nunes-Ferreira, A; Lima, G; Aguiar-Ricardo, I; Rigueira, J; Santos, R; Rodrigues, T; Cunha, N; Couto Pereira, S; S Morais, P; Sobral, S; et al.
Abstract: Introduction: Ablation of atrial fibrillation (AF) by catheter is an effective therapy, particularly in cases of refractoriness to medical therapy. Pulmonary vein isolation (PVI) has a significative long-term recurrence rate of AF, but the recurrence factors after this procedure are poorly defined. Purpose: To characterize the causes of AF recurrence after PVI and to evaluate complementary strategies that can optimize the therapeutic efficacy. Methods: A single centre prospective study of patients (pts) with AF submitted consecutively to PVI since September 2004. The variables responsible for the recurrence of AF, the complementary strategies of optimization of AF ablation and the occurrence of other dysrhythmias were evaluated. Results: A population of 521 pts were submitted to PVI as a primary strategy for AF treatment - 36.1% for paroxysmal AF, 32.5% for persistent AF <1 year, 14.5% persistent AF> 1 year. Eighty-three pts needed to perform 2 ablations and 10 pts performed 3 ablations. The higher the number of AF ablations, the higher the incidence of atypical atrial flutter (2% in the 1st AF ablation, 17% in the 2nd and 44% after 3 ablations). In the pts with recurrence of AF undergoing the 2nd ablation, it was verified that most of the pulmonary veins (PV) were not isolated, with an isolation rate of only 34.1% for the right inferior PV; 29.4% for superior PV right, 29.4% lower left VP, 28.2% upper left PV. In this group, in addition to a new PVI in the pts with re-conduction of PV, 45% performed complementary ablation strategies such as: ablation of the cavo-tricuspid isthmus (52.6%); ablation of the left atrium roof line (29%); mitral isthmus ablation line (26%); applications in the scar zone (26%); posterior atrial left line (8%), atrioventricular nodal reentrant atrioventricular ablation (5%), atrial tachycardia ablation (2.6%). In the pts submitted to the 3rd ablation, again a low PV isolation rate was confirmed: only 44.4% for the both left PV and upper right PV, and 55.6% for the right lower VP. 33.3% also performed cavo-tricuspid isthmus ablation, 22.2% lower mitral isthmus isolation and 22.2% re-isolation of gaps in the roof or intracicritricial line. Conclusion: This prospective study demonstrates a high rate of PV re-conduction after PVI and its role in AF recurrence. Therefore, the need for a more effective and definitive IVP technique is evident.